2008
DOI: 10.1007/s10815-008-9245-y
|View full text |Cite
|
Sign up to set email alerts
|

Thin unresponsive endometrium—a possible complication of surgical curettage compromising ART outcome

Abstract: Purpose Endometrial thickness is important for implantation. Little data addresses the etiology of persistently thin endometrium. We present a patient cohort in order to define common features and draw conclusions. Methods Thirteen out of 1,405 IVF patients repeatedly had thin unresponsive endometrium (<7 mm). Age, history, uterine cavity status, treatment type and outcome were examined. Results Patient age was 35.9±5.7 years. Ten patients had a curettage performed previously. Nine patients had normal cavity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…The initial purpose of endometrial curettage is complete examination and removal of malignant cells, so most of clinicians perform curettage thoroughly in all directions. However, this procedure can cause irreversible mechanical damage to the normal endometrial cells and lead to unresponsive endometrium [15]. Recently, several investigators demonstrated the efficacy of hysteroscopic resection of early stage EC combined with hormonal therapy [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The initial purpose of endometrial curettage is complete examination and removal of malignant cells, so most of clinicians perform curettage thoroughly in all directions. However, this procedure can cause irreversible mechanical damage to the normal endometrial cells and lead to unresponsive endometrium [15]. Recently, several investigators demonstrated the efficacy of hysteroscopic resection of early stage EC combined with hormonal therapy [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Not only does it occur after uterine cavity manipulation and infection (Shufaro et al, 2008), but it is also related to endocrine disorder, aging, and drug induction (Kumbak and Sahin et al, 2009;Le et al, 2013). The pathological and physiological characteristics of a thin endometrium were first described by Miwa et al (2009) as slow growth of the glandular epithelium, high resistance of the uterine artery blood flow, vascular dysplasia, and low expression of vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 99%
“…A thin endometrium it has been reported in 5 % of women <40 years of age and in 25 % of 41-45 years old women [18] and it has also been related to poor pregnancy outcome [20]. Regarding the etiology it is considered mainly idiopathic, however, a surgical complication postcurettage might be identified in some cases [19].…”
Section: Introductionmentioning
confidence: 99%